Epigenetic Regulation of Hepatic Stellate Cell Activation and Macrophage in Chronic Liver Inflammation - Shi, Chun-xia; Wang, Yao; Jiao, Fang-zhou; Chen, Qian; Cao, Pan; Pei, Mao-hua; Zhang, Lu-yi; Guo, Jin; Deng, Wei; Wang, Lu-wen; Gong, Zuo-jiong (Frontiers in Physiology, 2021)
Chronic liver inflammation is a complex pathological process under different stress conditions, the role of stellate cells and macrophages in chronic liver inflammation has been widely reported. Moderate liver inflammation can protect liver from damage and facilitate the recovery of liver injury. However, an inflammatory response that is too intense can result in massive death of hepatocytes, leading to irreversible damage to the liver parenchyma. Epigenetic regulation plays a key part in liver inflammation. This paper reviews the regulation of epigenetics on stellate cells and macrophages, for the purpose of exploring new mechanism of epigenetics on liver inflammation, providing new ideas for liver diseases therapy.